Notes on School Writing as a Truth Effect on the Subject or as a Gesture in the Subject's Relation to Knowledge - Manuela Cartolari; Jusmeidy Zambrano (Universidad Nacional, Costa Rica, 2013)
This paper discusses ethical and philosophical assumptions on how the writings of students are seen in the education context, in terms of subjectivity and knowledge.  Foucault's concept of power is associated to writing as a "truth-effect" on the subject and to the reified concept of the subject's writing, understood this as a mirror surface of thought. This stands in contrast to the spacing between the self and the sign implied in writing; spacing where subjectivity emerges, according to Derrida, in the sense produced by the difference. The conclusion suggests seeing writing as a gesture along the lines proposed by Agamben, because by overcoming the means-ends logic, the gesture becomes evident in the writing as a communication of communicability and of the pure power of thinking, i.e. an event. If, when writing, students are called to produce sense not only on a "specific" area of knowledge, but about their own selves within language as historical and desiring subjects, writing is assumed as a gesture toward knowledge, emerging therefore the ethical-political dimension on how we understand, evaluate and respond to students' writings.